PARTISIPASI PETANI PADA LUMBUNG PANGAN DALAM MENINGKATKAN KETERSEDIAAN PANGAN RUMAH TANGGA DI KECAMATAN AMBARAWA, KABUPATEN PRINGSEWU - Febrina Ramadhani; Indah Nurmayasari; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research aims to analyze the rate of household food availability, the rate of farmers’ participation, factors related to farmers’ participation rate, and the impact of the participation on the food availability. The research is a survey conducted in Ambarawa Subdistrict, Pringsewu District, as Ambarawa is an area that has many active food barns. Thirty food barn institutions were chosen randomly, and from each barn  two farmers were chosen randomly as respondents.  Research data is collected in September – November 2016 and analyzed by quantitative descriptive analysis method. The results showed that the rate of household food availability was 3,392.97 kkal/cap/day or equivalent to 2,135.58 kg of dried unhulled rice annually. The rate of farmers’ participation was included in a medium category. Age, membership time in barns, rice production, income, membership in farmer groups were not significantly related to farmers’ participation rate. Farmers’ participation did not have significant impact on food availability of farmer households. Key words: barns, farmer household, food availability, participation